(untitled) (Interdisciplinary Studies Journal, 2024)
Obesity is a global public health issue and causes various health problems in individuals. This problem has been intensely affecting children, as the incidence of overweight children increased dramatically during the pandemic. The aim of the study is to survey what national literature indicates regarding educational programs in early childhood education, focusing on changes in eating habits and physical activity practices for weight control. The methodology adopted was a systematic literature review, exploratory in nature and with a qualitative approach. The consultation of studies was conducted in the Google Scholar database during the months of May and June 2024. This reality demands the implementation of programs in early childhood education that promote changes in eating habits and encourage physical activity. One aspect that helps with children’s weight control and can be addressed within the school.